2002
DOI: 10.1259/bjr.75.890.750185
|View full text |Cite
|
Sign up to set email alerts
|

Adult intussusception—a CT diagnosis

Abstract: Intussusception, usually thought of as a childhood condition, may be encountered in adults as well, and is then more often associated with underlying pathology. While the condition is mostly unsuspected clinically, as patients present with non-specific abdominal pain that is often of long duration, CT findings are characteristic. Examples are shown of intussusception both in the small bowel and colon. Awareness of these findings allows the radiologist to make the correct diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
172
1
25

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(199 citation statements)
references
References 12 publications
1
172
1
25
Order By: Relevance
“…Case Report mass (10). In contrast, the most common imaging modalities used to image enteric duplication cysts is US.…”
Section: Discussionmentioning
confidence: 99%
“…Case Report mass (10). In contrast, the most common imaging modalities used to image enteric duplication cysts is US.…”
Section: Discussionmentioning
confidence: 99%
“…Intussusception was preoperatively diagnosed by abdominal ultrasonography with the target and doughnut signs on transverse view and the pseudokidney sign in the longitudinal view [1] . Intussusception was preoperatively diagnosed by multi-slice spiral computed tomography (CT) scans with the characteristic target or sausage sign, edematous bowel wall and mesentery in the lumen [4,5] .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, with the signs of target or sausage, mesenteric fat and vessels, abdominal CT scan has been reported to be the most useful imaging technique, with a diagnostic accuracy is 58%-100% [3][4][5]7,8] . Recent studies have demonstrated the superiority of CT in revealing the site, level, and cause of intestinal obstructions and in demonstrating threatening signs of bowel nonviability [9,10] .…”
Section: Figure 3 Efferent Loop Intussusception With a Tubementioning
confidence: 99%
“…However, obesity and the presence of massive air in the distended bowel loops limit the image quality and the subsequent diagnostic accuracy. Recently, with the target or sausage sign, abdominal CT scan has been reported to be the most useful imaging technique, with a diagnostic accuracy is 58%-100% [2,7,8,12,[17][18][19] . In our series 86.6% patients were diagnosed preoperatively by this technique.…”
Section: Discussionmentioning
confidence: 99%